La Banque du Canada était-elle nécessaire? - Chisholm, Derek (L'Actualité économique, 1983)
AbstractTraditional historiography has inferred that the Canadian government has failed to exercise control over the issue of high powered money during the interwar gold standard period. From this, it was concluded that the Canadian monetary constitution required modifications through the establishment of a central bank. This paper provides new evidence that the Canadian government did exercise monetary control during the period of the interwar gold standard regime and that Canada's record of adherence to the gold standard rules compares favourably with the performance of several other countries.